Pensamento Político Liberal e Doutrina Social Católica na Formação do Estado Brasileiro - Leite, Bruno Celso Sabino (2010)
The objective of this work was to analyze the construction of the Brazilian State in the second half of the nineteenth century, via debates, conflicts and accommodations between Liberal and Catholic thoughts, considering the establishment and organization of public instruction in the country. The study was developed intending to create links between history and political thought a history-problem which "observe" the past not by itself, but as a key to understand the problems of the present, especially the political and the social ones. Using official documents of the Catholic Church and the speeches of ecclesiastics members of the Brazilian parliament, we tried to understand what were their proposals for public education in Brazil in opposition to liberal political thought. In contrast, the liberal thought was also analyzed from point of view of "classic" texts of some well known thinkers in modenity and also of Brazilian political subjects in the nineteenth century, concerned with the issue of public instruction, and that, somehow, established connections with liberalist thoughts. Among these, as a sample and attempt to understand liberalism in Brazil, it was highlighted the work of Diogo Antônio Feijó, in the first half of the nineteenth century; Tavares Bastos, in the transition to the second half, and Rui Barbosa in the late nineteenth century and early twentieth century.